Best walks of the top end of the Northern Territory - Peart, Andy (Warriewood, NSW : Woodslane Press, 2021)
Best Walks of the Top End includes over 25 walks in this much-loved region, well-known for its spectacular national parks: Kakadu, Nitmiluk and Litchfield. Each walk specifies the distance, the total ascent and descent (if appropriate), the grade and the estimated duration and is accompanied by an accurate full-colour map. Snippets about the Top Ends' history, culture and wildlife add colour and interest to the walking experience. Families will enjoy information regarding child-friendly walks, and how to explore the bush safely with children of all ages. Over 100 full-colour photos complement the text, and provide the reader with a clear sense of the features on each walk. This guide will help walkers discover many of the classic walks in the region, as well as some wild and adventurous tracks that few know exist.
Series title from www.booktopia.com.au.
Includes index.
Keywords: Walking -- Northern Territory -- Guidebooks; Hiking -- Northern Territory -- Guidebooks; National parks and reserves -- Northern Territory -- Guidebooks; Lifestyle, Hobbies & Leisure; Travel & holiday; Northern Territory -- Guidebooks; Australia -- Description and travel; Australian; Guidebooks